Upper Midwest Environmental Science Center sand prairie as a model for identification and classification of plants in a middle school science classroom - Hoffman, Nicole (My University, 2011)
Project 2061's Benchmarks for Science Literacy provides educators with specific learning goals that should b used as a basis for curriculum development. The lesson, based on Project 2061's Benchmarks for Science Literacy, provides middle school science teachers with curriculum framework, referred to as a lesson plan, to have students observe basic plant structures and use that basic knowledge to be able to identify a plant. This lesson engages students in the opportunity to observe the similarities and differences in many different types of plants. Students identify plants using a basic field guide. That basic field guide organizes related plants based on families. Students become familiar with how plants are classified by related groups of organisms into families. Once students feel comfortable identifying and classifying plants, they have tools and skills to research the interdependence of life of a particular plant community.
Keywords: Upper Midwest Environmental Sciences Center (Geological Survey); Plants -- Classification; Plants -- Identification; Science -- Study and teaching (Middle School)